Decision science housing and community development : localized and evidence-based responses to distressed housing and blighted communities /: localized and evidence-based responses to distressed housing and blighted communities. (2015) - Johnson, Michael P; Keisler, Jeffrey M; Solak, Senay; Turcotte, David A; Bayram, Armagan; Bogardus Drew, Rachel
No abstract available